ISO 37001: Anti Bribery Management System - Implementation and Benefits - Nurul Khair, Ishak; Hasnah, Haron; Ishak, Ismail; Siti Zabedah, Saidin (Universiti Malaysia Pahang, 2017)
Anti-Bribery Management System standard, ISO37001 was first introduced in Malaysia on 15th October 2016. Other countries such as United Kingdom (UK) and the United States of America (USA) have adopted the same standard. Related Acts to support the standard, includes the US Foreign Corrupt Practices Act which was enacted in 1977 and amended in 1988, and the UK Bribery Act 2010 which was enacted on 8 April 2010 and was effective on 1 July 2011. The UK Bribery Act, 2010 was passed on 8 April 2010 and was enforced on 1 July 2011 and the US Foreign Corrupt Practices Act, was enacted in 1977 and was amended in 1988. This paper will discuss the purpose of ISO 37001, how to implement the system, and the benefits that can be gained from implementing it.